2021
DOI: 10.1038/s41586-020-03173-9
|View full text |Cite
|
Sign up to set email alerts
|

Half a century of global decline in oceanic sharks and rays

Abstract: Overfishing is the primary cause of marine defaunation, yet individual species' declines and rising extinction risk are difficult to measure, particularly for the largest predators found in the high seas 1-3 . We calculate two well-established indicators to track progress towards Aichi Biodiversity Targets and Sustainable Development Goals 4,5 : the Living Planet Index (a measure of changes in abundance aggregating 57 abundance time-series for 18 oceanic shark and ray species), and the Red List Index (a measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
442
0
5

Year Published

2021
2021
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 487 publications
(454 citation statements)
references
References 52 publications
7
442
0
5
Order By: Relevance
“…Regardless of the relative contribution of morphological versus behavioural mechanisms in driving patterns of diel activity, this study has demonstrated the importance of diel temporal variability as a niche partitioning axis in a marine predator guild for the first time. Recent and historical work suggests that healthy marine ecosystems are almost always characterized by abundant and diverse predator populations, although such healthy or pristine systems are unfortunately becoming increasingly rare [70,71]. Considering that many species of sharks tend to share space with other species as both juveniles and adults, and often display an overlap in prey and hierarchical predation that would incite interference competition, diel temporal niche partitioning may be an important factor in allowing multiple shark species to coexist in a variety of ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the relative contribution of morphological versus behavioural mechanisms in driving patterns of diel activity, this study has demonstrated the importance of diel temporal variability as a niche partitioning axis in a marine predator guild for the first time. Recent and historical work suggests that healthy marine ecosystems are almost always characterized by abundant and diverse predator populations, although such healthy or pristine systems are unfortunately becoming increasingly rare [70,71]. Considering that many species of sharks tend to share space with other species as both juveniles and adults, and often display an overlap in prey and hierarchical predation that would incite interference competition, diel temporal niche partitioning may be an important factor in allowing multiple shark species to coexist in a variety of ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…Much of this manuscript has tended toward the optimistic: introducing the possibilities and promise inherent to an industry showing initial signs of moving beyond short-term operational priorities to exploring the dimensions of stewardship. But a bitter reality of swift degradation of the biosphere cannot be ignored (Halpern et al, 2008;Crespo et al, 2019;Duarte et al, 2020;Pacoureau et al, 2021). The urgency of slowing and reversing current trajectories is omnipresent, as illustrated by a growing proportion of overfished stocks, a 70% loss of global shark and ray populations in 50 years, the rapid spread of antimicrobial resistance, and a dozen more grim statistics (Wernli et al, 2017;FAO, 2020;Lau et al, 2020;Pacoureau et al, 2021).…”
Section: Toward Ocean Stewardshipmentioning
confidence: 99%
“…But a bitter reality of swift degradation of the biosphere cannot be ignored (Halpern et al, 2008;Crespo et al, 2019;Duarte et al, 2020;Pacoureau et al, 2021). The urgency of slowing and reversing current trajectories is omnipresent, as illustrated by a growing proportion of overfished stocks, a 70% loss of global shark and ray populations in 50 years, the rapid spread of antimicrobial resistance, and a dozen more grim statistics (Wernli et al, 2017;FAO, 2020;Lau et al, 2020;Pacoureau et al, 2021). The future of the ocean and humanity's relationship with it may rest on efforts to translate stewardship from an aspirational notion to a pillar of standard operating procedure anchored in supportive public policy.…”
Section: Toward Ocean Stewardshipmentioning
confidence: 99%
“…Available at http://cmarpacifico.org/web-cmar/quienes-somos/que-es-el-cmar/. (Pacoureau et al, 2021) and a main reason for the decline of many migratory marine species in the ETPO (Peñaherrera-Palma et al, 2018, p. 71, 112). As well as intense fishing pressure from national vessels (WildAid, 2010, p. 2;The Economist, 2020;Hearn et al, 2021, p. 8), the high seas areas in this region have been subject to increased fishing effort in recent years by foreign flagged fleets, often loitering adjacent to or entering a marine protected area (Alava and Paladines, 2017;Collyns, 2020), a trend which is predicted to worsen in the future.…”
Section: Eastern Tropical Pacific Oceanmentioning
confidence: 99%